ADJUSTMENT OF TER RATES FOR INCOME TAX ARTICLE 21 FOR CORPORATE TAXPAYERS IN CV. KIRANA CAHAYA SEJAHTERA GUNUNGSITOLI - Fonahia Ndruru; Sophia Molinda Kakisina (Jurnal Suluh Pendidikan, 2026)
This study aims to establish the calculation, withholding, and reporting system for CV employees as per Article 21 of the ITC. Kirana Cahaya Sejahtera aims to resolve existing employee calculation, withholding, and reporting system issues under Article 21 of the Income Tax Code. This study utilised a saturated sampling technique with a population and sample size of 12 individuals. The researcher used a descriptive research methodology. The data collection methods comprised observation, interviews, and documentation. The collected data were analysed using qualitative descriptive techniques and deductive and inductive methods. The study results indicate the calculation of Income Tax Article 21 payable on Rendi's income for 2024, excluding the most recent tax period, as follows: Calculation of Income Tax Article 21 for each tax period. September = Rp 15,500,000 7% = Rp 1,085,000, October = Rp 15,500,000 7% = Rp 1,085,000, November = Rp 15,500,000 7% = Rp 1,085,000, and December = Rp 15,500,000. The total gross income is Rp 62,000,000 and the tax due under Article 21 is Rp 3,255,000. Determine income tax liability under Article 21 for the most recent tax period, which ended in December. Gross annual income is Rp 62,000,000.00. Annual office expenses deductions: 5% of Rp 62,000,000.00, with a maximum of 4 times Rp500,000.00, totalling Rp2,000,000.00. The pension contribution is 4 times Rp100,000.00, which equals Rp400,000.00. The total of Rp2,400,000.00 signifies the system's calculation, deposit, and reporting of Article 21 Income Tax for employees at CV. Kirana Cahaya Sejahtera is satisfactory. The company has been unable to deduct Article 21 Income Tax in accordance with the Tax Law. Overtime pay, as per Law No. 58 of 2023, is a component that boosts gross income. A discrepancy arises in the underpayment of Article 21 Income Tax withheld by the company and the researcher due to this consideration.